Characterisation of Plant Derived Damnacanthal and Nordamnacantbal Induced Cytotoxicity on Human HT29 Colon Adenocarcinoma Cell Line - Khor, Tin Oo (2001)
Nordamnacanthal and damnacanthal are two anthraquinones isolated from the roots of Morinda elliptica. They were found to exhibit cytotoxic activity against HT29 human colon adenocarcinoma cells. The cytotoxic concentrations of damnacanthal and nordamnacanthal that inhibited 50% growth (IC₅₀) of HT29 were 17 µg/ml and 7 µg/ml respectively. For the comparative purposes, the ICsos of several cytotoxic drugs against HT29 were also determined. The inhibition effect of nordamnacanthal was found to be comparable to etoposide (IC₅₀ = 7 µg/ml). cisplatin (IC₅₀ = 5 µg/ml) and doxorubicin (IC₅₀ = 6 µg/ml). The compound was found to be less active than methotrexate (MTX) (IC₅₀ < 0.05 µg/ml) and leunase (IC₅₀ = 2 µg/ml). On the other hand, the cytotoxic effect of damnacanthal was less active as compared to all cytotoxic drugs. However both compounds were found to be less toxic against non-cancerous fibroblast 3T3 ceJJs with the ICsos of 30 /lglml (damnacanthal) and 21 /lglm] (nordamnacanthal) respectively. Furthermore, damnacanthal and nordamnacanthal were found to induce apoptosis on HT29 cells at their ICso concentration as demonstrated by conventional agarose gel electrophoresis and also morphological alterations. DNA laddering was obtained after 12 hours of treatment by both compounds in a dose-independent but time-dependent fashion. Both compounds also caused cell death with apoptotic features such as cell shrinkage, membrane blebbing, nuclear fragmentation, and the presence of apoptotic bodies. In addition, caspase-3 was found to be activated during the execution of apoptosis induced by these compounds. This caspase activation was inhibited by a peptide based general caspase inhibitor, benzyloxycarbonyl-Val-Ala-Asp (OMe) fluoromethylketone (Z-V AD-FMK). In conclusion, this study demonstrates the potential antitumor activites of damnacanthal and nordamnacanthal.